2022
DOI: 10.1101/2022.11.08.515672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compressive sensing of neuronal connectivity maps from subsampled, cell-targeted optogenetic stimulation of a network model

Abstract: Mapping functional connectivity between neurons is an essential step towards probing the neural computations mediating behavior. The ability to consistently and robustly determine synaptic connectivity maps in large populations of interconnected neurons is a significant challenge in terms of yield, accuracy and experimental time. Here we developed a compressive sensing approach to reconstruct synaptic connectivity maps based on random two photon (2p) cell-targeted optogenetic stimulation and membrane voltage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…In accordance with previous predictions 72, 74 , we observed that, under low connectivity rate (k ≤10%), higher F values, and therefore better coverage of the population, improved reconstruction performances (Fig. S10B-E).…”
Section: Network Reconstruction Using Compressive Sensing: Simulation...supporting
confidence: 92%
See 4 more Smart Citations
“…In accordance with previous predictions 72, 74 , we observed that, under low connectivity rate (k ≤10%), higher F values, and therefore better coverage of the population, improved reconstruction performances (Fig. S10B-E).…”
Section: Network Reconstruction Using Compressive Sensing: Simulation...supporting
confidence: 92%
“…To increase the throughput of connectivity mapping, we tested a parallel approach where we activated sub-groups of putative presynaptic neurons simultaneously and applied compressive sensing (CS) to reconstruct connectivity from the evoked postsynaptic response 72,74 . CS gives conditions under which a system of equations can be solved with fewer measurements than unknowns.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations